Demographics and Haematological Parameters in Patients with Type II Diabetes Mellitus in Uttar Pradesh – A Comparative study - Priyanka Singh; Pradakhshana Vijay; Shaleen Chandra; Sanjay Kumar Singh; Diksha Singh; Priya Devi (Indian Journal of Dental Research)
Introduction: Pathophysiology and clinical relevance of haematological parameters in various populations have always been a keen interest of research for haematologists. Various factors may have a role in the values of serum biochemical parameters. These might include gender, age, altitude and disorders like diabetes mellitus, hypertension or both. Aim: To compare the demographics and haematological parameters like haemoglobin, white blood cell and platelet values in type II diabetes mellitus patients. Materials and Method: Record of 1,200 patients, who came to the haematology section of the department in the regular outpatient department (OPD) services, was randomly selected from the daily record data. The record of selected patients was categorized into Group A – (Control group) subjects with no morbidity and Group B – patients with diabetes mellitus type II. Blood parameters of each were noted and analysed in the Department of Oral Pathology and Microbiology. Results and Discussion: The study found no significant association between age and gender and diabetes occurrence. However, there was a significant difference in total leukocyte count (TLC) levels, particularly in males, among diabetics. Additionally, there was a significant variation in platelet count among diabetics, with more variation in females. Conclusion: We found a significant positive correlation between TLC and the platelet count among males and females of diabetes mellitus patients. This surely affects the lifestyle and general health, and so the patients must be educated and motivated to maintain a regular blood sugar level through diet, exercise and medicines as poor control can definitely lead to complications.